Schaum's outline of theory and problems of physical chemistry - Metz, Clyde R. (New York : McGraw Hill Education, 1988)
Schaum's Outlines present all the essential course information in an easy-to-follow, topic-by-topic format. You also get hundreds of examples, solved problems, and practice exercises to test your skills.
Chapter 1. Gases and the kinetic-molecular theory -- Chapter 2. Translation and transport phenomena -- Chapter 3. First law of thermodynamics -- Chapter 4. Thermochemistry -- Chapter 5. Entropy -- Chapter 6. Free energy -- Chapter 7. Chemical equilibrium -- Chapter 8. Statistical thermodynamics -- Chapter 9. Electrochemistry -- Chapter 10. Heterogeneous equilibria.
Includes index.
Keywords: CHEMISTRY, PHYSICAL AND THEORETICAL PROBLEMS, EXERCISES, ETC